Learning and Memory Impairment in High Fat Diet Induced Obesity - Ariani, Citra; Ibrahim, Nurhadi; Yolanda, Sophie (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
Obesity is a manifestation of abnormal fat accumulation which can lead to impairment in several organs, including the brain. Neuroinflammation is considered the cause of cell death as well as reactive oxygen species in hippocampal neuron cells. It results in disturbance of memory forming process. Impaired learning and memory function affects a person's ability to carry out daily tasks and lower quality of life over time, so they should be circumvented with preventive, curative, and rehabilitative measures. The understanding of the pathological mechanisms of obesity-induced memory impairment based on the changes at molecular levels is imperative for an effective management. We collected and reviewed research articles to summarize the pathological mechanisms. Twenty studies were included in this review in terms of signaling pathway, molecular markers in brain and changes in memory and behavior pattern. It is showed that memory changes in obesity could be resulted from inflammation, impaired neurogenesis and cell senescence via various mechanisms and pathways. In conclusion, the understanding of the pathomechanisms in obesity-induced memory impairment aids to its the prevention and treatment.